Astrocytes and Inflammatory T Helper Cells: A Dangerous Liaison in Multiple Sclerosis - Kunkl, Martina; Amormino, Carola; Tedeschi, Valentina; Fiorillo, Maria Teresa; Tuosto, Loretta (Frontiers in Immunology, 2022)
Multiple Sclerosis (MS) is a neurodegenerative autoimmune disorder of the central nervous system (CNS) characterized by the recruitment of self-reactive T lymphocytes, mainly inflammatory T helper (Th) cell subsets. Once recruited within the CNS, inflammatory Th cells produce several inflammatory cytokines and chemokines that activate resident glial cells, thus contributing to the breakdown of blood-brain barrier (BBB), demyelination and axonal loss. Astrocytes are recognized as key players of MS immunopathology, which respond to Th cell-defining cytokines by acquiring a reactive phenotype that amplify neuroinflammation into the CNS and contribute to MS progression. In this review, we summarize current knowledge of the astrocytic changes and behaviour in both MS and experimental autoimmune encephalomyelitis (EAE), and the contribution of pathogenic Th1, Th17 and Th1-like Th17 cell subsets, and CD8+ T cells to the morphological and functional modifications occurring in astrocytes and their pathological outcomes.